A 3D detailed micro-model for the in-plane and out-of-plane numerical analysis of masonry panels. (15th August 2018) - D'Altri, Antonio Maria; de Miranda, Stefano; Castellazzi, Giovanni; Sarhosis, Vasilis
Highlights: A 3D detailed micro-model for the numerical analysis of masonry panels is proposed. Textured units are composed by brick and mortar nonlinear plastic-damaging finite elements. Textured units are assembled by means of rigid-cohesive interfaces. Experimental-numerical comparisons are provided for masonry panels and positive results are obtained. The direct characterization of all the mechanical properties from small-scale tests is guaranteed. Abstract: In this paper, a novel 3D detailed micro-model to analyse the mechanical response of masonry panels under in-plane and out-of-plane loading conditions is proposed. The modelling approach is characterized by textured units, consisting of one brick and few mortar layers, represented by 3D solid finite elements obeying to plastic-damage constitutive laws. Textured units are assembled, accounting for any actual 3D through-thickness arrangement of masonry, by means of zero-thickness rigid-cohesive-frictional interfaces, based on the contact penalty method and governed by a Mohr-Coulomb failure surface with tension cut-off. This novel approach can be fully characterized by the properties obtained on small-scale experimental tests on brick and mortar and on small masonry assemblages. The interface behaviour appears consistent with small-scale tests outcomes on masonry specimens. Experimental-numerical comparisons are provided for the in-plane and out-of-plane behaviour of masonry panels. The accuracy, the potentialities and the efficiency of the modelling approach are shown and discussed.